Impaired vocal communication, sleep‐related discharges, and transient alteration of slow‐wave sleep in developing mice lacking the GluN2A subunit of N‐methyl‐d‐aspartate receptors. (3rd June 2019) - Salmi, Manal; Del Gallo, Federico; Minlebaev, Marat; Zakharov, Andrey; Pauly, Vanessa; Perron, Pauline; Pons‐Bennaceur, Alexandre; Corby‐Pellegrino, Séverine; Aniksztejn, Laurent; Lenck‐Santini, Pierre‐Pascal; Epsztein, Jérôme; Khazipov, Rustem; et al.
Abstract: Objective: Glutamate‐gated N ‐methyl‐d ‐aspartate receptors (NMDARs) are instrumental to brain development and functioning. Defects in the GRIN2A gene, encoding the GluN2A subunit of NMDARs, cause slow‐wave sleep (SWS)‐related disorders of the epilepsy‐aphasia spectrum (EAS). The as‐yet poorly understood developmental sequence of early EAS‐related phenotypes, and the role of GluN2A‐containing NMDARs in the development of SWS and associated electroencephalographic (EEG) activity patterns, were investigated in Grin2a knockout (KO) mice. Methods: Early social communication was investigated by ultrasonic vocalization (USV) recordings; the relationship of electrical activity of the cerebral cortex with SWS was studied using deep local field potential or chronic EEG recordings at various postnatal stages. Results: Grin2a KO pups displayed altered USV and increased occurrence of high‐voltage spindles. The pattern of slow‐wave activity induced by low‐dose isoflurane was altered in Grin2a KO mice in the 3rd postnatal week and at 1 month of age. These alterations included strong suppression of the delta oscillation power and an increase in the occurrence of the spike‐wave bursts. The proportion of SWS and the sleep quality were transiently reduced in Grin2a KO mice aged 1 month but recovered by the age of 2 months. Grin2a KO mice also displayed spontaneous spike‐wave discharges, which occurred nearly exclusively during SWS, at 1 and 2 months of age. Significance: The impaired vocal communication, the spike‐wave discharges occurring almost exclusively in SWS, and the age‐dependent alteration of SWS that were all seen in Grin2a KO mice matched the sleep‐related and age‐dependent manifestations seen in children with EAS, hence validating the Grin2a KO as a reliable model of EAS disorders. Our data also show that GluN2A‐containing NMDARs are involved in slow‐wave activity, and that the period of postnatal brain development (postnatal day 30) when several anomalies peaked might be critical for GluN2A‐dependent, sleep‐related physiological and pathological processes.